1H NMR-based kinetic and theoretical studies of the simultaneous formation of two discrete rotameric systems of a novel difenchyl sulfite ester. Issue 49 (7th December 2017) - Singh, Alicia; Kaye, Perry T.; Lobb, Kevin A.
Abstract: Attempted repetition of a reported synthesis of fenchene from fenchol has afforded, in high overall yield, a mixture shown by spectroscopic and elemental analysis to comprise a pair of discrete rotameric systems of a novel 2- endo -2′- endo -difenchyl sulfite ester. The kinetics of the formation of these dimeric rotameric systems (I andII ) has been explored experimentally, using 1 H NMR spectroscopic analysis, and theoretically at molecular and quantum mechanical levels. Construction of a theoretical model has permitted calculation of rate constants for each of the steps, while modelling of the transition state complexes corresponding to the rate-determining steps for the formation of the rotameric systemsI andII has revealed their independent access to further sets of interconverting rotamers. Graphical abstract: